Perceived value influences on disruption in the context of life insurance : a study on the influence of value dimensions on perceived value in the life insurance industry in South Africa and the resulting impact on disruption in this context - Chipp, Kerry (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.